Information needs and mHealth applications for carers of people with dementia in managing behavioural and psychological symptoms of care recipients: an integrative review protocol - Samath Dharmaratne; Thilanka Jagoda; Sarath Rathnayake (BMJ Open)
Introduction This integrative review aims to synthesise, appraise and analyse the evidence on informal carers’ information needs, features and functions of available mHealth applications, and informal carers’ usability and engagement with mHealth applications for managing behavioural and psychological symptoms of dementia (BPSD).Methods and analysis This integrative review will include quantitative, qualitative and mixed-methods studies and follow the ‘Preferred Reporting for Systematic Reviews and Meta-Analyses 2020’ guidelines. Peer-reviewed articles published in English from 2000 to 2021 will be included from Cochrane Library, CINHAL, Embase, MEDLINE, ProQuest and PsycINFO. Five broader concept categories will be included: ‘dementia’, ‘behavioural and psychological symptoms’, ‘informal carers’, ‘(information need’ OR ‘mHealth application)’. In title and abstract review, first, the researchers will independently screen 10% of sources for consensus, and one reviewer will screen the rest. In full-text review, two reviewers will conduct the screening process and assess the relevancy of the full-text articles using a two-point scale (high-low) and the methodological quality of included articles using the Mixed Methods Appraisal Tool. Narrative synthesis will be employed to synthesise themes. The findings may identify the need for planning interventions for carers of people with dementia concerning the management of BPSD.Ethics and dissemination Ethics approval not required. This review will be published in a peer-review journal and be presented at national and international conferences.PROSPERO registration number CRD42021238540.